Pap Smear Screening and HPV Vaccination Among Jordanian Women: Sociocultural and Economic Barriers - A. Negresh, Nour; Al-Sheyab, Ruba F.; Albdaren, Nour; Alayasra, We'am; Ayasrah, Batool; Almomani, Abdullah; Alkhalaileh, Ahmad; Alkhdour, Yaman; Khaza'leh, Ahmad; Nsoor, Alaa Al; et al. (Journal of Neonatal Surgery, 2025)
Background: Cervical cancer is the eleventh most frequent cancer among Jordanian women. Around 115 women are diagnosed with cervical cancer, though 71 women die of cervical cancer annually in Jordan. Incorporating pap smear screening into routine gynecological care will contribute to the early detection and prevention of cervical cancer. Screening for cervical cancer should begin at the age of 21 or within three years of becoming sexually active. Objectives: The study aims to assess the awareness and knowledge of Jordanian married females about the role of pap smear screening in the detection of cervical cancer. This research also aims to discover the barriers that determine the application of Pap smears in Jordan. Methods: A cross-sectional study will be conducted, involving about 770 married women aged between 22-50 years old in Jordan. Data will be collected for demographic information like age. Various clinical characteristics will be analyzed. Statistical analyses will be performed using R studio (version 2024.09.0) Vienna, Austria. Results: Although 83.7% of participants had heard of cervical cancer, only 31% had had a Pap smear, and just 7.1% did so regularly. Higher education and income were linked to greater awareness and screening uptake. Cultural barriers like embarrassment (9.9%) and fear of the procedure (8.1%) limited participation, while spousal disapproval was minimal. Awareness of the HPV vaccine was very low (9.9%), and only 1.9% had received it, mainly due to lack of knowledge and fear of side effects. Regional and income disparities also affected screening rates. Conclusion: The study shows a gap between awareness of cervical cancer and actual screening behavior among Jordanian women. Education, income, and cultural beliefs strongly influence Pap smear uptake. Low awareness and uptake of the HPV vaccine highlight the need for targeted health education and accessible preventive services. Improving provider communication, community outreach and affordability are important to enhancing cervical cancer prevention efforts in Jordan.